Determinants of food demand among urban households in Minna Metropolis, Niger State, Nigeria - Obalola, Oyeyode Tohib; Tanko, Likita; Aboaba, Kazeem Oriyomi; Abubakar, Bello Bunza; ODUM, Emmanuel Egbodo Boheje; Agboola, Babatola Olasunkanmi; Ibrahim, Kobe Hussein; Audu, Rabiu Omeiza; Danilola, Samuel Temitope (Journal of Agriculture and Natural Resources, 2021)
Agricultural products including rice, yam and cowpea play significant roles in the food consumption of urban dwellers. However, increase in crop production cost has continued to threaten urban food price in Nigeria. This study analyzed the determinants of demand for food commodities among urban households in Minna metropolis. Data were collected from 110 household heads of urban residences, which were selected through a three-stage random sampling technique. Data collected for the study were analyzed using multiple regression technique. The results showed that rice, yam and cowpea were price in-elastic. The cross-price elasticities for rice, yam and cowpea were -0.132, 0.028 and 0.005 respectively. The computed own price, cross price and income elasticity of demand for rice were –0.308, -0.132 and 0.018 respectively. For yam, the computed values were -1.262, 0.028 and 0.289 respectively. While for cowpea, these values were -0.530, 0.005 and 0.002 respectively. For the income elasticity, rice and cowpea were proven to be normal goods and yam as a luxury good. The social protection strategies in form of food aids policy should be put into action to minimize the inflationary pressure on food items in the urban areas.